Impacts of accidents with workers in rock processing industries: Short review - André do Couto (2018)
Natural stone production is a major economic sector in many countries around the world. However, are many parameters of difficult control in the materials handling operations that make it one of the most risky industrial activities. Workers in this sector are exposed to significant risks namely in the activities of unloading and storing plates and blocks, cutting and polishing plates, assembling ornamental pieces and loading the final products. This work aims to study the impacts of the accidents with workers in the rock processing industries and the characterization of its causes and effects in this industrial sector. As base of this research was used PRISMA Statement approach. From the 20,436 articles found, 7 matches the research question and were deeply analyzed. According to this research, occupational accidents are the leading causes of death or serious injury and injuries to the upper limbs are an important part of occupational accidents.